Reliability of countermovement jump estimation using the Chronojump jump mat: intra-session and within-session - Villalon-Gasch, L.; Jimenez-Olmedo, J. M.; Aparicio-Aparicio, I.; Sanchis-Sanchis, R. (Journal of Physical Education and Sport, 2024)
Vertical jump is a fundamental metric for monitoring and regulating lower body capacities, especially in assessing sports performance through the countermovement jump (CMJ). In recent years, various instruments aimed at estimating vertical jump heights have emerged. However, ensuring effective performance monitoring requires that jump mats prove consistency in measuring jumps across repeated tests, i.e., they must prove reliability. This study focuses on evaluating the intra-session and within-session test-retest reliability of the Chronojump jump mat in highly trained female volleyball players. Ten athletes from the Spanish Superliga 2 league participated in 100 CMJs over two sessions spaced a week apart. A repeated measures design collected jump height data using Chronojump jump mat. The protocol included a 10-min warm-up, a 5-min rest, and the execution of 5 CMJs with 2 min of rest between trials. Intra-session test-retest consistency was assessed by analyzing consecutive pairings of the first five trials. The study reveals moderate noise for SEM (1.56 cm) and standardized SEM (0.37), accompanied high SDC (4.33 cm) and SWC (0.44 cm). Correlation analysis indicated very high reliability (ICC =0.89), high concordance (CCC = 0.82) and a moderate CV (5.97%). Regarding within-session reliability, no significant differences were observed (Paired t-test p = 0.08; Hedges effect size g = 0.09). Additionally, very high correlations between both sessions were observed (r = 0.86). Absolute reliability analysis revealed a noise of 1.65 cm (SEM), resulting in high SDC (4.59 cm) and SWC (0.47 cm). Relative reliability, assessed through correlation coefficients, displayed very high values (ICC = 0.89 and CCC =0.89), although a moderate standardized SEM of 0.44 was observed. The Bland-Altman plot indicated systematic errors of the mean of 0.41 cm without substantial dispersion. Linear regression analyses between sessions showed a high correlation (r = 0.86), with a systematic error of 6.65 cm (intercept) and a random error of 2.01 cm (SEE). To sum up, the Chronojump jump mat proves reliability in measuring CMJ in female volleyball players across both intra-session and within-session contexts. High reliability suggests that this instrument can be deemed reliable for such measurements.